Inflammatory biomarkers as predictors of immune activation to different irradiated sites and short-term efficacy in advanced squamous cell esophageal carcinoma received radioimmunotherapy - Li, Mengying; Cai, Guoxin; Gao, Zhenhua; Meng, Xue; Han, Xiao (Frontiers in Oncology, 2023)
Purpose: The present study aimed to compare immune activation among different irradiated sites and identify potential short-term efficacy prognostic factors in patients with advanced squamous cell esophageal carcinoma (ESCC) who received radiotherapy (RT) and immunotherapy. Patients and Methods: We recorded the clinical characteristics, blood cell counts, and derived blood index ratios, including neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), platelet-to-lymphocyte ratio (PLR), and systemic immune-inflammation index (SII), at three time points (before, during, and after RT) in 121 patients with advanced ESCC who had received RT and immunotherapy. Chi-square test and univariate and multivariate logistic regression analyses were used to calculate the relationships among inflammatory biomarkers (IBs), irradiated sites, and short-term efficacy. Results: Delta-IBs were calculated as (medio-IBs - pre-IBs) ÷ pre-IBs. The medians of delta-NLR, delta-SII, and delta-ANC were the lowest, whereas the median of delta-LMR was the highest in patients with brain radiation. Treatment responses were observed within 3 months after RT or until the beginning of the next line therapy, and the disease control rate (DCR) was 75.2%. The areas under the receiver operating characteristic curve (AUCs) for delta-NLR and delta-SII were 0.723 (p = 0.001) and 0.725 (p < 0.001), respectively. Multivariate logistic regression analysis showed that the treatment lines of immunotherapy (odds ratio [OR], 4.852; 95% confidence interval [CI], 1.595-14.759; p = 0.005) and delta-SII (OR, 5.252; 95% CI, 1.048-26.320; p = 0.044) were independent indicators of short-term efficacy. Conclusions: In this study, we found that RT to the brain had a stronger immune activation effect than RT to extracranial organs. We also found that earlier-line immunotherapy plus RT and a decrease in SII during RT may generate better short-term efficacy in advanced ESCC.